2021
DOI: 10.1371/journal.pone.0253147
|View full text |Cite
|
Sign up to set email alerts
|

Associations between early postoperative pain outcome measures and late functional outcomes in patients after knee arthroplasty

Abstract: Introduction/Aim Early rehabilitation, return to daily life activities and function are the ultimate goals of perioperative care. It is unclear which pain-related patient-reported outcome measures (PROM) mirror treatment effects or are related with early and late functional outcomes. Methods We examined associations between two approaches of pain management (scheduled vs ‘on demand’) and PROMs on post-operative days one and five (POD1, 5) with function on POD5 and 3 months after surgery in patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…In general, knee pain is known to occur after TKA, and Seo et al reported that 60% of patients who underwent TKA experienced severe postoperative knee pain, whereas 30% experienced moderate pain [ 22 ]. Also, the previous study investigated the association between pain on postoperative days one and five and motor function at three months, and the results showed that the less pain in the early postoperative period, the better the motor function at three months postoperatively [ 23 ]. It is also well-known that pain in the early postoperative period is associated with improved knee joint ROM, pain, and walking speed three months after TKA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, knee pain is known to occur after TKA, and Seo et al reported that 60% of patients who underwent TKA experienced severe postoperative knee pain, whereas 30% experienced moderate pain [ 22 ]. Also, the previous study investigated the association between pain on postoperative days one and five and motor function at three months, and the results showed that the less pain in the early postoperative period, the better the motor function at three months postoperatively [ 23 ]. It is also well-known that pain in the early postoperative period is associated with improved knee joint ROM, pain, and walking speed three months after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well-known that pain in the early postoperative period is associated with improved knee joint ROM, pain, and walking speed three months after TKA. Therefore, improving physiotherapeutic interventions to decrease pain in the early postoperative period is necessary to control for improving knee joint ROM and walking functions [ 23 ]. The results of this study showed that one week of FR intervention on the anterior thigh from the second postoperative week resulted in a significant ( p = 0.031) reduction in pain score at stretching (−26.0 ± 1.4) as compared with the control group (−12.5 ± 1.9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, postoperative pain relief in hip fracture patients was shown to promote early functional gait recovery [10]. Such a positive correlation was also seen in patients undergoing knee arthroplasty, where postoperative pain management was associated with better range of motion, better performance in daily activities, and faster gait speed [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although total knee arthroplasty (TKA) is currently a reliable treatment for end-stage osteoarthritis patients with pain and disability, 11% to 18% of postoperative patients are dissatisfied with the procedure (2,3). Chronic postsurgical pain (CPSP), defined as pain lasting for more than three months after surgery, is regarded as a critical factor of postoperative dissatisfaction (3)(4)(5). Although CPSP has attracted much attention in the academic community, prolonged analgesic use (PAU), which often accompanies CPSP, has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%